Mean queue time approximation of tandem queues with finite buffer - Tan, Phyllinda Shu Ning. (2013)
Tandem queues are the fundamental structure of queuing networks. Existing studies on tandem queues have mostly assumed infinite buffer capacities in order to approximate mean queue times. However, this is not possible in practical production environments due to limited floor space.